Fabrication of low emissivity paint for thermal/NIR radiation insulation for domestic applications - H.M. Fayzan Shakir; Aiman Ali; Usman Zubair; Tingkai Zhao; Z.A. Rehan; Imran Shahid (Energy Reports, 2022)
Recently, low-emissivity paint has gained more importance than commercial paints. Low emissivity (Low-E) Paint also termed as a coating for radiation control, in which the emissivity of radiations of longer waves are reduced dramatically (i.e., the emissivity of commercially available paint is 0.9) by imparting low emissivity particles in the base paint but not suitable to reduce near-infrared radiation. Commercially available paints as of today have minimum of 0.7 emissivity and it does not give any significant energy saving. The low emissivity property of paint makes it particularly suitable for reducing the radiative heat exchange in many domestic applications i.e., home electronics, building construction components, roof surfaces, heat storage tanks, and pipes, etc in result, low power required to heat or cool the building in respective whether conditions. In this work, different samples of white paint were prepared in the lab by using a low shear mixer (mechanical stirrer) under very controlled conditions and studied the results of dry paint films to reduce the thermal emissivity then commercially available paint. Then we investigate the drying time of the wet paint films and analyze thermal heat into visible light through thermal imaging camera, Crosshatch, and IR transmission. We also studied the emissivity through ET-100 and aging stability through a weather-o-meter instrument, which investigated that emissivity value achieved in the range of 0.4–0.6 than commercial paints. The results showed that paint exhibits an acceptable aesthetic emissivity value of ∼0.60. It was calculated theoretically that by the use of this novel Low-E paint, annually about 20%–25% less energy will be consumed in building for cooling or heating.